2012
DOI: 10.1088/0004-637x/756/1/40
|View full text |Cite
|
Sign up to set email alerts
|

THEHERSCHELEXPLOITATION OF LOCAL GALAXY ANDROMEDA (HELGA). II. DUST AND GAS IN ANDROMEDA

Abstract: We present an analysis of the dust and gas in Andromeda, using Herschel images sampling the entire far-infrared peak. We fit a modified-blackbody model to ∼4000 quasi-independent pixels with spatial resolution of ∼140 pc and find that a variable dust-emissivity index (β) is required to fit the data. We find no significant long-wavelength excess above this model suggesting there is no cold dust component. We show that the gas-to-dust ratio varies radially, increasing from ∼20 in the center to ∼70 in the star-fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
171
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 146 publications
(195 citation statements)
references
References 72 publications
(121 reference statements)
23
171
1
Order By: Relevance
“…This value is about 1.1 dex higher than the simulated galaxy dust mass (see Table 1 for the galaxy parameters). Similarly, the median value of the dust-to-stellar mass ratio found by Smith et al (2012) for a spiral galaxy sample in the HRS survey is also a factor 10 higher than the simulated galaxy value. The scatter in the empirical values (≈ 0.2 dex) is not large enough to account for the discrepancy.…”
Section: Intrinsic Galaxy Stellar Emission Opacity and Gas Mass Distmentioning
confidence: 70%
See 1 more Smart Citation
“…This value is about 1.1 dex higher than the simulated galaxy dust mass (see Table 1 for the galaxy parameters). Similarly, the median value of the dust-to-stellar mass ratio found by Smith et al (2012) for a spiral galaxy sample in the HRS survey is also a factor 10 higher than the simulated galaxy value. The scatter in the empirical values (≈ 0.2 dex) is not large enough to account for the discrepancy.…”
Section: Intrinsic Galaxy Stellar Emission Opacity and Gas Mass Distmentioning
confidence: 70%
“…Chary & Elbaz 2001, Compiègne et al 2011, Dale et al 2001 c 0000 RAS 2002, , Natale et al 2010 or single temperature modified black body curves (e.g. Amblard et al 2010, Bourne et al 2012, Dariush et al 2011, Smith et al 2012). In addition, empirically constrained proxies for star formation rates based on a variety of observational tracers are in common use (see Buat et al 2010, Kennicutt & Evans 2012, Calzetti et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The dust radiation can be approximated as a "graybody" radiation, with the emissivity ν β , where the emissivity index β is related to the physical properties and the environment of dust grains. For instance, Ade et al (2011) gave the median value of β for our Galaxy as 1.8; Smith et al (2012) found that β varies from 1.7 to 2.5 in the Andromeda Galaxy using Herschel data. In order to compare FIR temperature with the literature, we fix the β value to 1.6 as suggested in Leipski et al (2013).…”
Section: Extra Dust Componentmentioning
confidence: 89%
“…There are a number of problems with this approach, however. One complication is the notoriously uncertain value of the dust emissivity at long wavelengths (Bianchi et al 2003;Kramer et al 2003;Alton et al 2004;Shirley et al 2011) and the mysterious anti-correlation between the dust emissivity index and dust temperature (Dupac et al 2003;Shetty et al 2009;Veneziani et al 2010;Juvela & Ysard 2012b,a;Kelly et al 2012;Smith et al 2012a). A second problem is the difficulty to observe in the FIR/submm window, which necessarily needs to be done from space using cryogenically cooled instruments.…”
Section: Introductionmentioning
confidence: 99%
“…This poor spatial resolution limits a detailed study of the dust medium to the most nearby galaxies only (e.g. Meixner et al 2010;Bendo et al 2010Bendo et al , 2012Xilouris et al 2012;Foyle et al 2012;De Looze et al 2012b;Fritz et al 2012;Smith et al 2012a;Galametz et al 2012). Moreover, several authors have demonstrated that even estimating total dust masses from global fluxes induces an error due to resolution effects (Galliano et al 2011;Galametz et al 2012).…”
Section: Introductionmentioning
confidence: 99%